Analisis Perubahan Kebijakan Kerja Sama Luar Negeri Argentina dengan Tiongkok dalam Bidang Pembangunan Nuklir - Santika Dewi, Ida Ayu Alit; Sushanti, Sukma; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
The offer of cooperation from China to build nuclear in Argentina is one of the biggest cooperation between the two countries. However, the cooperation was postponed by Argentina in 2018 due to the economic crisis. In the midst of crisis that have not yet improved, Argentina under the government of President Mauricio Macri is planning to re-sign the cooperation which has drawn various responses from the public and other countries. However, through various considerations, the Argentine government finally re-signed the agreement in 2019. In this paper, researchers use a qualitative explanative method with rational actor model and the concept of national interest to explain the policy changes made by the Argentine government. Then, this research finds that the reason Argentina re-signed nuclear cooperation with China is that the benefits refer to the fulfillment of national interests and have been calculated with the opportunity cost.   Keywords: Argentina, Nuclear, Rational Actor Model, National Interest